Shifting in the Dominant Bacterial Group Endozoicomonas Is Independent of the Dissociation With Coral Symbiont Algae - Shiu, Jia-Ho; Yu, Sheng-Ping; Fong, Chia-Ling; Ding, Jiun-Yan; Tan, Chih-Jui; Fan, Tung-Yung; Lu, Chih-Ying; Tang, Sen-Lin (Frontiers in Microbiology, 2020)
The coral-associated Endozoicomonas are dominant bacteria in the coral holobiont. Their relative abundance usually decreases with heat-induced coral bleaching and is proposed to be positively correlated with Symbiodiniaceae abundance. It remains unclear whether this phenomenon of decreased Endozoicomonas abundance is caused by temperature stress or a decreased abundance of Symbiodiniaceae. This study induced bleaching in the coral Euphyllia glabrescens using a dark treatment over 15 weeks. We examined shifts in Endozoicomonas abundance and experimentally reduced Symbiodiniaceae density. 16S rRNA gene amplicon sequencing was used to characterize the changes in bacterial community (incl. Endozoicomonas) over time, and the 16S rRNA gene copy number of Endozoicomonas was quantified by qPCR. We detected a high abundance of Endozoicomonas in E. glabrescens that underwent dark-induced bleaching. The results reveal that changes in the relative abundance of Endozoicomonas are unrelated to Symbiodiniaceae abundance, indicating that Endozoicomonas can be independent of Symbiodiniaceae in the coral holobiont.